Talent Management Challenges in the Pandemic Covid-19 era - Hendry Kurniawan; Andy Afrizal; Seprini (Pusat Riset dan Inovasi Nasional, 2022)
The most significant company assets are Human Resources (HR). Talent management is very important to attract and maintain competent employees. The purpose of this study is to see the challenges of talent management in the Pandemic Covid-19 era. Qualitative methods in the form of literature reviews are used in this study. Literature research was conducted by examining in six publications on talent management in the Pandemic Covid-19 era published in national and international journals between 2017 and 2021. The greatest difficulty for human management during Pandemic, according to the results of the analysis, was that organizations and businesses in the whole world are currently facing a very volatile situation. The organization must respond and adapt to changes, and manage their workforce, in the context of global change brought by the plague. Therefore, the organization must constantly try to be proactive to deal with reality that is always changing and unpredictable.